AKIBAT HUKUM TERHADAP PERKAWINAN DARI LAKI-LAKI YANG MENIKAHI DUA PEREMPUAN SECARA BERSAMAAN - Risti Febiawati; Mardalena Hanifah; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Marriage has a very important position in social life. In Indonesia, there are four laws thatregulate marriage issues, namely the Civil Code, the Marriage Law, the Compilation of Islamic Law andIslamic Law, stipulating the reasons for allowing polygamy. But in reality, there are cases of marriages ofmen marrying two women simultaneously without fulfilling the terms and conditions that have been set.The purpose of this thesis is to find out the legal consequences of the marriage of a man who marries twowomen at the same time. Second, to find out the legal position of the marriage of a man who marries twowomen simultaneously according to the Marriage Law, Compilation of Islamic Law, Civil Code andIslamic Law.This type of research is classified in the type of normative juridical research using literaturereview. Namely by making a legal comparison between the Marriage Law, Compilation of Islamic Law,Civil Code, and Islamic Law, the approach is carried out using a qualitative analysis approach bylooking for data in books, journals and other scientific works related to this research. The data sourcesused are secondary data covering primary and secondary legal materials.The conclusions obtained from the results of the study are first , the legal position of marriagefor men who marry two women simultaneously in the Marriage Law and the Compilation of Islamic Lawdoes not exist, this is because this marriage is included in sirri polygamy. The position of marriagesimultaneously in Islamic law since the marriage contract is held, the position of husband and wives is thesame. Second, the legal consequences of marriages of men who marry two women simultaneously in theMarriage Law and the Compilation of Islamic Law is an illegitimate marriage so that it does not causelegal consequences. The Civil Code adheres to the principle of monogamy so that if a polygamousmarriage occurs, Article 279 of the Criminal Code will apply. According to Islamic law, this concurrentmarriage is a legal marriage and is allowed by religion.Keywords: Marriage–Polygamy–Marriage Simultaneously